Fruit bar from mango (Mangifera indica Linn var. carabao) puree Carlita A. Ajero ; Mayi Y. Arcellana, adviser. - Ajero, Carlita A. (1979)
The study was designed to develop a fruit bar from mango puree by cabinet dehydration. To obtain such a product, the study was divided into three phases. Phase I involved the determination of the most preferred binder-sugar combination to be added to the mango puree. In Phase I-A, 5% and 10% cornstarch by weight were added into the 25° and 30° Brix soluble solids levels. Phase I-B concerned the addition of 0.5% and 1.0% pectin by weight into the same soluble solids levels as in Phase I-A. Finished products were tested objectively and presented to a 10-member panel for sensory evaluation. Sensory evaluation data were statistically analyzed to ascertain the best combination. The 25° Brix with 5% cornstarch and 1.0% pectin were found to be the most satisfactory combinations. The best combinations selected in Phase I-A and Phase I-B were subjected to 5 and 10 minutes cooking in Phase II. Cooking temperatures were 180°F for samples with cornstarch and 160°F for those with pectin. Fruit pastes were tested for consistency and finished products were subjected to sensory evaluation. Results indicated that fruit bars cooked for 5 and 10 minutes at 25° Brix soluble solids with 1.0% pectin were the most preferred products. In Phase III, the cabinet drying temperature in relation to cooking time was determined. The products were tested objectively and sensory evaluation was conducted. Statistical analysis of the panel scores showed that the fruit bar cooked for 5 minutes and cabinet dried at 160°F for 135 minutes had better sensory qualities and hence most preferred by the panelists. Cost evaluation revealed that it was the cheapest among the four pro